Newly Developed Software Application for Multiple Access Process Planning. (18th November 2014) - Monkova, Katarina; Monka, Peter
Abstract : The purchase of a complex system for computer aided process planning (CAPP) can be expensive for little and some middle sized plants, sometimes an inaccessible investment, with a long recoupment period. According to this fact and the author's experience with Eastern European plants, they decided to design a new database application which is suitable for production, stock, and economic data holding as well as processing and exploitation within the manufacturing process. The application can also be used to process a plan according to the selected criteria, for technological documentation and NC program creation. It was based on the theory of a multivariant approach to computer aided plan generation. Its fundamental features, the internal mathematical structure and new code system of processed objects, were prepared by the authors. The verification of the designed information system in real practice has shown that it enables about 30% cost and production time reduction and decreases input material assortment variability.